1982
DOI: 10.21236/ada125650
|View full text |Cite
|
Sign up to set email alerts
|

Alternatives to Overcome the Communications Problem of Formal Requirements Analysis.

Abstract: C ") 0 ABSTRACT (Continue on reverse side If necesseary and Identify by block number) Lu] 'Even in spite of formal requirements analysis, problems persist in the full-J acceptance of software systems. These problems are basically due to communica-LA. tions problems between users and system experts. C_. This paper discusses some alternative approaches to overcome these problems. It weights their relative advantages and shortcomings against each other. The Capproaches discussed are: Objectives Analysis, Prototyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…There has been increasing awareness of the impact of the early stages of the systems development process on the quality of the information systems that are ultimately delivered. A critical early activity is requirements definition, when the requirements for an information system are determined and expressed as a requirements specification (Mittermeir et al, 1987;Greenspan et al, 1994). Significant difficulties can arise during subsequent development activities if requirements specifications are incomplete, unclear or incorrect (Roman, 1985;Curtis et al, 1988), and difficulties and inadequacies in requirements have been identified as a major factor in information systems failures (Boehm, 1981;Lyytinen & Hirschheim, 1987).…”
Section: Abstract: Requirements Analysis Requirements Definition VImentioning
confidence: 99%
“…There has been increasing awareness of the impact of the early stages of the systems development process on the quality of the information systems that are ultimately delivered. A critical early activity is requirements definition, when the requirements for an information system are determined and expressed as a requirements specification (Mittermeir et al, 1987;Greenspan et al, 1994). Significant difficulties can arise during subsequent development activities if requirements specifications are incomplete, unclear or incorrect (Roman, 1985;Curtis et al, 1988), and difficulties and inadequacies in requirements have been identified as a major factor in information systems failures (Boehm, 1981;Lyytinen & Hirschheim, 1987).…”
Section: Abstract: Requirements Analysis Requirements Definition VImentioning
confidence: 99%
“…The requirements identification involves the user in a communication process. Effective communication is needed to support the collaborative behaviors necessary for requirements elicitation (Mittermeir, Hsia, & Yeh, 1987; Bostrom, 1989; Newman & Robey, 1992).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Models in information systems development attempt to overcome the ambiguity of natural language. However, Mittermeir et al (1982) point out that although notation is an important element for efficient communication, both the communicator and the recipient must understand the notation used. Proponents of systems development models hold the view that the notation adopted is intuitive, requiring little explanation.…”
Section: Languagementioning
confidence: 99%
“…The members of the community entered have a subjective view of their environment and consider the holistic impact of changes, they are only interested in technology to the extent of its impact on their work. Mittermeir et al (1982) describe this distinction between views as users and systems developers holding different frames of reference. The users perceive a holistic system to adopt in the environment in which they are submerged while analysts decompose the system into objects, data, processes, volumes and time constraints.…”
Section: Cognitionmentioning
confidence: 99%